Contribution of enhanced engagement of antigen presentation machinery to the clinical immunogenicity of a human interleukin (IL)‐21 receptor‐blocking therapeutic antibody. (5th November 2015) - Xue, L.; Hickling, T.; Song, R.; Nowak, J.; Rup, B.
Summary: Reliable risk assessment for biotherapeutics requires accurate evaluation of risk factors associated with immunogenicity. Immunogenicity risk assessment tools were developed and applied to investigate the immunogenicity of a fully human therapeutic monoclonal antibody, ATR‐107 [anti‐interleukin (IL)‐21 receptor] that elicited anti‐drug antibodies (ADA) in 76% of healthy subjects in a Phase 1 study. Because the ATR‐107 target is expressed on dendritic cells (DCs), the immunogenicity risk related to engagement with DC and antigen presentation pathways was studied. Despite the presence of IL‐21R on DCs, ATR‐107 did not bind to the DCs more extensively than the control therapeutic antibody (PF‐1) that had elicited low clinical ADA incidence. However, ATR‐107, but not the control therapeutic antibody, was translocated to the DC late endosomes, co‐localized with intracellular antigen‐D related (HLA‐DR) molecules and presented a dominant T cell epitope overlapping the complementarity determining region 2 (CDR2) of the light chain. ATR‐107 induced increased DC activation exemplified by up‐regulation of DC surface expression of CD86, CD274 (PD‐L1) and CD40, increased expansion of activated DC populations expressing CD86 hi, CD40 hi, CD83 hi, programmed death ligand 1 (PD‐L1) hi, HLA‐DR hi or CCR7 hi, as well as elevated secretion of tumour necrosis factor (TNF)‐α by DCs. DCs exposed to ATR‐107 stimulated an autologous T cell proliferative response in human donor cells, in concert with the detection of immunoglobulin (Ig)G‐type anti‐ATR‐107 antibody response in clinical samples. Collectively, the enhanced engagement of antigen presentation machinery by ATR‐107 was suggested. The approaches and findings described in this study may be relevant to identifying lower immunogenicity risk targets and therapeutic molecules.